Trends in Hospitalization, Acute Kidney Injury, and Mortality in Patients With Spontaneous Bacterial Peritonitis. Issue 2 (February 2019) - Devani, Kalpit; Charilaou, Paris; Jaiswal, Palashkumar; Patil, Nirav; Radadiya, Dhruvil; Patel, Pranav; Young, Mark; Rockey, Don C.; Reddy, Chakradhar M.
Abstract : Goals: The purpose of our study was to evaluate trends of hospitalization, acute kidney injury (AKI) and mortality in cirrhotic patients with spontaneous bacterial peritonitis (SBP). Background: SBP is a frequent bacterial infection in cirrhotic patients leading to increased morbidity and mortality. Materials and Methods: A total of 4, 840, 643 patients hospitalized with cirrhosis from 2005 to 2014 were identified using the Nationwide Inpatient Sample database, of which 115, 359 (2.4%) had SBP. We examined annual trends and used multivariable mixed-effects logistic regression analyses to obtain adjusted odds ratios by accounting for hospital level and patient level variables. Results: We identified a striking increase in hospitalizations for SBP in cirrhotic patients (0.45% to 3.12%) and AKI in SBP patients (25.6% to 46.7%) from 2005 to 2014. Inpatient mortality decreased over the study period in patients with SBP (19.1% to 16.1%) and in patients with SBP plus AKI (40.9% to 27.6%). Patients with SBP had a higher inpatient mortality rate than those without SBP [15.5% vs. 6%, adjusted odd ratio (aOR): 2.02, P <0.001]. AKI was 2-fold more prevalent in cirrhotics with SBP than those without SBP (42.8% vs. 17.2%, aOR: 1.91, P <0.001) and concomitant AKI was associated with a 6-fold mortality increase (aOR: 5.84, P <0.001). Cirrhotic patients with SBP had higher hospitalization costs and longer length of stays than patients without SBP. Conclusions: Despite a higher hospitalization rate and prevalence of concomitant AKI, mortality in patients with SBP decreased during the study period. SBP is associated with high likelihood of development of AKI, which in turn, increases mortality.